Improving Patient-Centered Care through Process Optimization in Medical Clinics: A Review - Allabbas, Hadi Mansour Mohsen; Alabbas, Sultan Mansour; Al-Munjam, Ali Muhammad; Al Abbas, Youssef Muhammad Mansour; Al Abbas , Muhammad Manea Salam; Alabbas , Saleh Mohammed Mansour; Alabbas, Ibrahim Mahdi Mari; Al Zamanan , Mahdi Mania; Al-Salloum, Mansour Hadi Ali; Al rawas, Nasser Ali Saleh (Journal of Ecohumanism, 2024)
Objective: This review explores the role of process optimization in enhancing patient-centered care in medical clinics. By analyzing strategies such as Lean Six Sigma, digital tools, and workflow redesign, it examines how these interventions improve patient satisfaction, streamline communication, and reduce inefficiencies in care delivery. Methods: A systematic search of PubMed, Scopus, and Web of Science was conducted, focusing on studies published between 2016 and 2024. Inclusion criteria encompassed peer-reviewed articles and case studies that evaluated the impact of process optimization strategies on patient-centered outcomes in medical clinics. Data synthesis followed PRISMA guidelines. Results: The review included 32 studies across various clinical settings. Key findings demonstrated that process optimization significantly improved patient satisfaction by reducing waiting times and enhancing communication. Digital health technologies facilitated more seamless care coordination, while Lean methodologies addressed inefficiencies in patient flow. Common barriers to implementation included staff resistance, resource constraints, and technological challenges. Conclusion: Process optimization is essential for advancing patient-centered care in medical clinics. While challenges persist, the benefits of these strategies are substantial, highlighting their potential for broader adoption. Future research should focus on addressing implementation barriers and evaluating the long-term sustainability of these interventions.